Stereospecific actions of 2,5-dimethoxy-4-methylamphetamine (DOM) on colonic temperature in the rat at various ambient temperatures. - Beaton, J M (1976)
The R(-) and S(+)-isomers of 2,5-dimethoxy-4-methylamphetamine (DOM) produce a dose-dependent hypothermia in rats kept in the cold (6 degrees C). 2 This hypothermia was linearly dependent upon ambient temperature and the R(-)-isomer was considerably more potent than the S(+)-isomer. 3 A statistically significant tachyphylaxis was observed when R(-)-DOM was administered on two successive days. The response seven days after the second injection was similar to that on the first day of injection. 4 The hypothermia induced by R(-) and S(+)-DOM was antagonized by methysergide but not by p-chlorophenylalanine (PCPA) or pimozide. Methysergide, PCPA or pimozide alone did not elicit hypothermia at the doses used. The results indicate that R(-) and S(+)-DOM act at post-synaptic 5-hydroxytryptamine receptors.